Effect of the monsoon forecast announcement on stock returns - Viswanathan Nagarajan (Elsevier, 2021)
The Indian summer monsoon rainfall (ISMR) has considerable influence on the Indian economic and corporate performance. Therefore, the announcement of long-range ISMR forecasts by the Indian Meteorological Department can be expected to impact stock returns significantly. We find that the initial ISMR forecast announcement is associated with statistically significant post-announcement cumulative average abnormal returns (CAARs) for CNX 500 stocks. The CAARs are positive for forecasts of normal ISMR and negative for forecasts of below normal ISMR. Further, we report statistically significant pre-announcement CAARs which unexpectedly are positive for both types of forecasts. We also provide evidence indicating that investors rationally allocate their attention towards pricing the effect of the ISMR forecast on large stocks.